PERAN KEPEMIMPINAN KEPALA SEKOLAH MEMODERASI KOMPETENSI DAN KOMITMEN GURU TERHADAP KINERJA GURU (Studi pada Yayasan Pondok Modern Selamat Kendal) - 11.52.02.0134, Mastur Hasyim (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study was to determine the effect of Competence and Commitment to Performance Master Teacher Principal Leadership as moderation . This research was conducted on the entire teachers SMP , SMA Yayasan Pondok Modern Selamat Kendal, amounting to 106 teachers. Statistical analysis of the results obtained that ( 1 ) Teachers Competency gives positive and significant impact to teachers ( 2 ) Teachers Commitment gives positive and significant impact to the performance of teachers ( 3 ) Principal leadership has positive and significant effect to the teachers performance ( 4 ) Principal Leadership moderate of competence gives positive and significant effect to the performance of teachers , ( 5 ) Principal Leadership moderate of Commitment gives positive and significant effect to the performance of teachers . Moderation test proves that the head of School Leadership as moderating variables that affect the performance of the teachers contributor. Keywords : leadership , competence , commitment and Teacher Performance.